2017
DOI: 10.1128/aac.00654-17
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Concentration of Piperacillin during Continuous Infusion in Critically Ill Patients

Abstract: This retrospective cohort study included 53 patients admitted to the intensive care unit (ICU), with an average age of 69 years, without neurologic disorder before initiation of a continuous piperacillin infusion at the standard dose and who underwent piperacillin serum concentration monitoring. Among them, 23 developed a neurologic disorder for which the piperacillin causality was chronologically and semiologically suggestive. A concentration threshold of 157.2 mg/liter independently predicted neurotoxicity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 15 publications
1
50
0
1
Order By: Relevance
“…To achieve the target of 100% f T > 1×MIC, the applied dose needs to be increased many-fold irrespective of the licensed regimen or EI, as illustrated in Figure 5, leading to high peak concentration and exposure, with potential toxicity issues 40 . The target of 50% f T > 4×MIC is achieved at doses of 40–80 mg/kg for an MIC of 4.0 mg/L by administering piperacillin as a 3 h EI q8h, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve the target of 100% f T > 1×MIC, the applied dose needs to be increased many-fold irrespective of the licensed regimen or EI, as illustrated in Figure 5, leading to high peak concentration and exposure, with potential toxicity issues 40 . The target of 50% f T > 4×MIC is achieved at doses of 40–80 mg/kg for an MIC of 4.0 mg/L by administering piperacillin as a 3 h EI q8h, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to higher than defined SCs was associated with significantly higher With regard to adverse effects, Imani et al [37] demonstrated neuro-and nephrotoxicity during bolus application of PIP. Quinton et al [38] predicted neurotoxicity following continuous application of PIP at around a threshold concentration of 157 mg/L with a sensitivity of 52% which implies that neurotoxicity might well happen above and below 157 mg/L that concentration. Noticeably, patients with neurotoxic symptoms showed a significantly lower eGFR (18 mL/min) as compared to those without neurotoxicity (50 mL/min).…”
Section: Discussionmentioning
confidence: 99%
“…Overexposure to these agents is a primary risk factor for neurotoxicity . Piperacillin was also associated with neurotoxicity in cases of overexposure . Even in the context of ARC, empirical dose escalation beyond doses approved by the Food and Drug Administration (FDA) may not be appropriate given the risk of toxicity and the relative lack of data linking ARC to lower β‐lactam CNS concentrations.…”
Section: Identifying Patients At Risk For Arcmentioning
confidence: 99%